PENGARUH CUSTOMER RELATIONSHIP MARKETING, KEUNGGULAN PRODUK DAN NILAI NASABAH TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK RIAU SYARIAH PEKANBARU - Arsyad, Arsyad; Samsir, Samsir; Restuti, Sri (Jurnal Ekonomi, 2017)
The purpose of this research are: 1) To analyze the effect of customerrelationship marketing on customer loyalty through customer satisfaction Bank Riau Syariah Pekanbaru. 2) To analyze the effect of product excellence tow ard customer loyalty through customer satisfaction Bank Riau Syariah Pekanbaru.3) To analyze the influence of customer value on customer loyalty through customer satisfaction Bank Riau Syariah Pekanbaru. 4) To analyze the effect of customer satisfaction on customer loyalty Bank Riau Syariah Pekanbaru.This research was conducted in Pekanbaru in Bank Riau Syariah Pekanbaru which take place in September 2015. As for the population in this study were all Customer Savings Bank Riau Syariah Pekanbaru totaling 66 021 people.Sampling using accidental sampling method that is 100 Customer Savings Bank Riau Syariah Pekanbaru, which incidentally met with investigators can be used as a sample. Data collection technique used by a questionnaire containing statements based on variables studied. Data were analyzed using path analysis.From the results obtained the following conclusions: 1) customer relationship marketing positive and significant impact on customer loyalty through customer satisfaction Bank Riau Syariah Pekanbaru. 2) The value of customers' positive and significant impact on customer loyalty through customer satisfaction Islamic Bank Riau in Pekanbaru. 3) Advantage positive and significant impact on customer loyalty through customer satisfaction Bank Riau Syariah Pekanbaru. 4) That the customer satisfaction and significant positive effect on customer loyalty Bank Riau Syariah Pekanbaru.